Anarchist voices : an oral history of anarchism in America - Avrich, Paul.; Paul Avrich Collection (Library of Congress) (Oakland, Calif. : AK Press, 2005)
"In Anarchist Voices, Avrich lets American anarchists speak for themselves. This book contains 80 interviews conducted by Avrich over a period of 30 years, interviews that portray the human dimensions of a movement much maligned by the authorities and contemporary journalists. Most of the interviewees (anarchists as well as their friends and relatives) were active during the heyday of the movement, between the 1880s and the 1930s. They represent all schools of anarchism and include both famous figures and minor ones, previously overlooked by most historians. Their stories provide a wealth of personal detail about such anarchist luminaries as Emma Goldman and Sacco and Vanzetti."--BOOK JACKET.
Includes bibliographical references (pages 537-542) and index.
Keywords: Anarchism -- United States -- History; Anarchists -- United States -- Interviews